Masjid Strategies in Improving Community Economy with Cooperatives (Case Study of Oman Al-Makmur Masjid): Strategi Masjid Dalam Meningkatkan Perekonomian Masyarakat Dengan Koperasi (Studi Kasus Masjid Oman Al-Makmur) - Arif, Weldy; Habibi, Khairul; Juhari, Juhari (Perisai : Islamic Banking and Finance Journal, 2025)
This study examines the role of the Oman Al Makmur Mosque in empowering the local community's economy through a sharia-based cooperative. The research focuses on assessing two main aspects: the mosque's role as a center of economic activity and the impact of the cooperative on the welfare of its members and the surrounding environment. A qualitative descriptive method was used, with data collected through in-depth interviews, observation, and documentation. The uniqueness of this study lies in its emphasis on the role of the mosque economy and the application of Qardhul Hasan in cooperative practices, which is rarely explored. The data were analyzed thematically to discuss issues of cooperative management, the implementation of the Qardhul Hasan mechanism, as well as the challenges and opportunities faced. This study also makes a significant contribution to the discourse on Islamic-based economic empowerment and provides practical guidance for mosque managers and financial institutions in supporting community-based MSMEs. The research results show that since its establishment in October 2022, the mosque cooperative has facilitated interest-free capital for more than 130 members to start and develop micro, small, and medium enterprises (MSMEs). Bank Indonesia and BPRS Hikmah Wakilah have strengthened access to capital. This research makes an important contribution to the discourse on Islamic-based economic empowerment and offers practical guidance for mosque managers and financial institutions in supporting community-based MSMEs. The uniqueness of this study lies in the emphasis on the role of the mosque economy and the application of Qardhul Hasan in cooperative practices, which are still rarely explored.